A study on fetomaternal outcome in eclampsia in a tertiary care institute - Dev, Sushma V.; Kadambi , Mythreyi; Meghana Devakki Nagaraj (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Eclampsia is a life threatening emergency that continues to be a major cause of maternal and perinatal mortality. The present study was undertaken to analyse the maternal and fetal outcome in patients of eclampsia and to evaluate various factors influencing this outcome. Methods: A retrospective observational epidemiological study was undertaken in the Department of Obstetrics and Gynecology, Mysore Medical College and Research Institute, Mysore, for a period of three years from January 2020 to December 2022. All women who presented as eclampsia or developed eclampsia during hospital stay were included in the study. Data analysed included various maternal parameters, fetal parameters, and the outcome of pregnancy. Results: The incidence of eclampsia was 7.14% which is relatively high, attributing to the fact that being tertiary care centre many cases are referred. Higher incidence seen in primigravida (72.4%) and low maternal age (48%). Caesarean section was indicated in 50% deliveries indicating immediate action was necessary for better fetomaternal outcome. 58.6% had an uneventful maternal outcome.There was 7.65% maternal mortality most common cause of death was intracranial hemorrhage. 53% were preterm deliveries and 29.4% stillbirths, respiratory distress in the newborn was seen as the major complication (41.9%). Conclusions: In our study, maternal complications were recorded in 41.3% of the patients with a case fatality rate of 7.65%. Respiratory distress, prematurity, growth restriction and low birth weight are the neonatal complications to be anticipated. We infer from our study that better antenatal care, early recognition of disease, timely referral, early initiation of treatment and termination of pregnancy in eclamptic women could improve maternal and fetal outcome.